Read Symbol defintion
-
Q01 |
- Highlights
-
Q02 |
- Method 1 : Prove that Sum[n^2)] = n*(n+1)*(2*n+1)/6
-
Q03 |
- Method 2 : Prove that Sum[n^2)] = n*(n+1)*(2*n+1)/6
-
Q04 |
- Method 3 : Prove that Sum[n^2)] = n*(n+1)*(2*n+1)/6
-
Q05 |
- Method 4 : Prove that Sum[n^2)] = n*(n+1)*(2*n+1)/6
-
Q06 |
- Patterns : Squres in squares
-
Q07 |
- Pattern : Numbers in square patterns
-
Q08 |
- Second difference of squaence 1, 4, 9, 16, 25, .....
-
Q09 |
- Home work
-
Q10 |
- Exercises
-
Q11 |
- Exercises
Answers
|
Q01. Highlight
- Pattern : Squares in squares
- Pattern : Numbers in square patterns
- Proof of the formula using 4 different methods
Go to Begin
Q2 Prove that 1^2 + 2^2 + 3^2 +...+ n^2 = n*(n+1)*(2*n+1)/6
* Method 1 : By observation
1^2 + 2^2 = 1 + 4 = 5 = 2*3*5/6
1^2 + 2^2 + 3^2 = 1 + 4 + 9 = 14 = 3*4*7/6
1^2 + 2^2 + 3^2 + 4^2 = 1 + 4 + 9 + 16 = 30 = 4*5*9/6
Since 4*5*9/6 = 4*(4+1)*(2*4+1)/6 for n = 4
Proof complete
Go to Begin
Q03. Prove that 1^2 + 2^2 + 3^2 +...+ n^2 = n*(n+1)*(2*n+1)/6
Method 2 : Use Sum[C(n+1,2)] = C(n+3,2)
C(n+1,2) = (n+1)*n/2!
C(n+2,3) = (n+2)*(n+1)*n/3!
Sum[(n+1)*n/2!] = (n+2)*(n+1)/3!
Expnand :
Sum[n^2 + n] = 2*(n+2)*(n+1)*n/6
Hence Sum[n^2] = 2*(n+2)*(n+1)*n/6 -Sum[n]
Since Sum[n] = n*(n+1)/2
Hence Sum[n^2] = n*(n+1)*[2*(n+2)/6 - 1/2]
Hence Sum[n^2] = n*(n+1)*(2*n+1)/6
Go to Begin
Q04. Prove that 1^2 + 2^2 + 3^2 +...+ n^2 = n*(n+1)*(2*n+1)/6
Method 3 : Use mathematical induction
n = 1 the sum is true
n = 2 the sum is true
n = k+1 should be true. i.e. S(k+1)=(k+1)*(k+2)*(2*(k+1)+1)/6 exists
n = k+1 and S(k+1) = S(k) + (k+1)^2
Hence S(k+1) = k*(k+1)*(2*k+1)/6 + (k+1)^2
Hence S(k+1) = (k+1)*(k*(2*k+1)/6 + (k+1))
Hence S(k+1) = ((k+1)*(2*k^2+k)/6 + k+1))
Hence S(k+1) = (k+1)*(2*k^2 + 7*k + 6)/6
Hence S(k+1) = (k+1)*(k+1+1)*(2*(k+1)+1)/6
Proof complete
Go to Begin
Q05. Prove that 1^2 + 2^2 + 3^2 +...+ n^2 = n*(n+1)*(2*n+1)/6
Method 4 : Use (a+b)^3 = a^3 + 3*(a^2)*b + 3*a*(b^2) + 1 ............(1)
- Since (x+1)^3 = x^3 + 3*x^2 + 3*x + 1
- Sum[(x + 1)^3 - x^3] = Sum[3*x^2] + Sum[3*x] + Sum[1]
- Sum[(x + 1)^3 - x^3]
- = (2^3 - 1) + (3^3 - 2^3) + ...... ((x+1)^3 - x^3)
- = (x + 1)^3 - 1 (All terms cancelled out expcept -1 and (x+1)^3)
- = x^3 + 3*x^2 + 3*x
- Hence Sum[3*x^2] + Sum[3*x] + Sum[1] = x^3 + 3*x^2 + 3*x ...... (2)
- From (1) and (2) we have
- Sum[3*x^2] + Sum[3*x] + Sum[1] = x^3 + 3*x^2 + 3*x
- Sum[3*x^2] = x^3 + 3*x^2 + 3*x - Sum[3*x] - Sum[1]
- Sum[3*n^2] = n^3 + 3*n^2 + 3*n - 3*n*(n+1)/2 - n
- = n^3 + 3*n^2 + 3*n - 3*n*(n+1)/2 - n
- = n^3 + 2*n + 3*n^2 - 3*n^2/2 - 3*n/2
- = n^3 + 3*n^2/2 + n/2
- = n*(2*n^2 + 3*n + 1)/2
- = n*(n+1)*(2*n+1)/2
- Hence Sum[n^2] = n*(n+1)*(2*n+1)/6
Go to Begin
Q06. Pattern :
Squares in squares
1 + 4 + 9 + 16 + ....
Go to Begin
Q07. Pattern : Numbers in square patterns
* .......... 1^2 = 1
* *
* * ........ 2^2 = 4
* * *
* * *
* * * ...... 3^2 = 9
Go to Begin
Q08. Find 2nd difference of sequence 1, 4, 9, 16, 25, 36,....
Sequence : 01 04 09 16 25 36 .....
1st diff : .. 03 05 07 09 11 .....
2nd diff : ..... 02 02 02 02 .....
Go to Begin
Q09. Home work :
a. Write all formulae used in above methods to note book.
b. Try to remember them
c. Fid more series which are given in Chapter 14 of MD2002
Go to Begin
Q10. Exercises :
a. Prove Sum[n^1] = (n*(n+1))/2 ........... See program 14 01
b. Prove Sum[n^2] = (n*(n+1)*(2*n+1)/6 .... See Program 14 12
c. Sequence 1, 4, 09, 16, 25, ...... Find the 10th term
c. Sequence 2, 5, 10, 17, 26, ...... Find the 10th term
Go to Begin
Q11. Reference
- MD2002 Program 14 13
- MD2002 text file ZS.txt
Go to Begin
|
|